Measuring Penang tourism destination attractiveness: application of contextual approach - Muhamad Aswad, Mohd Noor (2022)
The purpose of this study was to study the perception of destination attractiveness in Penang. The objective of the research is to study the importance of destination attractiveness attributes of tourists who have visited Penang. Quantitative methods were conducted and distribution of questionnaire were used in this study. A total of 400 respondents were participated in this study through online and face -to -face methods. Data were analyzed using SPSS software version 24. A total of 16 destination attractiveness attributes were selected and the findings of the study have shown that safety and security were the most important attributes that perceived by tourists who have visited Penang. The results of this study will contribute to the existing knowledge in the field of marketing and destination management